Air power history : turning points from Kitty Hawk to Kosovo - Cox, Sebastian; Gray, Peter W. (London ; Portland, OR : Frank Cass, 2002)
"The 20th century saw air power transformed from novelists' fantasy into stark reality. From string and canvas to precision weaponry and stealth, air power has progressed to become not only the weapon of first political choice, but often the only conceivable option. This rapid development has given rise to considerable debate and controversy with those holding entrenched views rarely slow to shout their case. Many myths have grown over the period, ranging from the once much-vaunted ability of air power to win wars alone through to its impact as a coercive tool.:--Publisher's website.
Learning in real time: the development and implementation of air power in the First World War / Tami Biddle -- Achieving air ascendancy: challenge and response in British strategic air defence, 1915-40 / John Ferris -- The Royal Naval Air Service: a very modern service / Christina J.M. Goulter -- The Luftwaffe and lessons learned in the Spanish Civil War / James S. Corum -- The Second World War as a turning point in air power / Richard P. Hallion -- Maritime air power and the Second World War: Britain, the USA and Japan / John Buckley -- A neglected turning point in air power history: air power and the fall of France / Stuart W. Peach -- 'Learning is winning': Soviet air power doctrine, 1935-41 / James Sterret -- The development of tactical air doctrine in North Africa, 1940-43 / Brad Gladman -- Logistics doctrine and the impact of war: the Royal Air Force's experience in the Second World War / Peter Dye -- Australia and the war in the Pacific, 1942-45 / Ian MacFarling -- Planning the air campaign: the Washington perspective / Diane Putney -- The 1991 bombing of Baghdad: air power theory vs Iraqi realities / John Andreas Olsen -- The Gulf War and UK air power doctrine and practice / Sebastian Cox and Sebastian Ritchie -- Solidifying the foundation: Vietnam's impact on the basic doctrine of the US Air Force / Mark Clodfelter -- Air power victorious? Britain and NATO strategy during the Kosovo Conflict / Sebastian Ritchie -- The Balkans: an air power basket case? / Peter W. Gray.
Includes bibliographical references and index.
Keywords: Geschichte 1914-1999; Air power -- History; Air warfare -- History; Aeronautics, Military; History